Toxigenic profile of methicillin-sensitive and resistant Staphylococcus aureus isolated from special groups - Souza, Camila Sena Martins [UNESP]; Fortaleza, Carlos Magno Castelo Branco [UNESP]; Witzel, Claudia Lima [UNESP]; Silveira, Mônica [UNESP]; Bonesso, Mariana Fávero [UNESP]; Marques, Silvio Alencar [UNESP]; Cunha, Maria de Lourdes Ribeiro de Souza da [UNESP] (Springer Nature, 2016)
Background: Staphylococcus aureus is characterized by its pathogenicity and high prevalence, causing disease in both healthy and immunocompromised individuals due to its easy dissemination. This fact is aggravated by the widespread dissemination of S. aureus carrying toxigenic genes. The objective of this study was to determine the toxigenic profile of methicillin-sensitive S. aureus (MSSA) and methicillin-resistant S. aureus (MRSA) in patients with purulent skin and/or soft tissue infections seen at the Dermatology Department of the University Hospital of the Botucatu Medical School, asymptomatic adults older than 60years living in nursing homes, and prison inmates of the Avaré Detention Center. Methods: PCR was used for the detection of the mecA gene, enterotoxin genes (sea, seb, and sec), exfoliative toxins A and B (eta and etb), toxic shock syndrome toxin 1 (tst), panton-valentine leukocidin (lukS-PV and lukF-PV), and alpha- and delta-hemolysins or cytotoxins (hla and hld). Results: The results showed a significant prevalence of toxigenic genes among S. aureus isolates from asymptomatic individuals, with the observation of a higher prevalence of cytotoxin genes. However, the panton-valentine leukocidin gene was only detected in MSSA isolated from patients with skin infections and the tst gene was exclusively found in MSSA isolated from prison inmates. Conclusions: The present study demonstrated a significant prevalence of toxigenic genes in MSSA and MRSA strains isolated from asymptomatic S. aureus carriers. There was a higher prevalence of cytotoxin genes.
Keywords: Cytotoxins; MSSA; Staphylococcus aureus; Toxins